Pola Sosialisasi Pendidikan Seksual Pada Anak Usia Dini Non Formal di SKB Ungaran Kabupaten Semarang - Choirina, Ernita; Arbarini, Mintarsih (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2023)
Sexual education in early childhood can be provided through parents and teachers at school. Parents and teachers work together to provide education to early childhood and look after each other so that the knowledge given can stick to children properly. Various patterns of socialization of sexual education have been given to students at PAUD SKB Ungaran, Semarang Regency, some of these socialization patterns include: using the storytelling method, showing illustrated videos of sexual education education that are suitable for early childhood, providing toys that are suitable for use in sexual education education in early childhood, provide explanations that are easy for children to understand. With these methods, children can know clearly how to protect their bodies or the dangers in the surrounding environment that could occur.